2022
DOI: 10.1097/md.0000000000029211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shift work on irritable bowel syndrome and functional dyspepsia

Abstract: Background: The possible association between shift work with irritable bowel syndrome (IBS) and functional dyspepsia (FD) remains controversial. The purpose of the study is to conduct a meta-analysis to explore the potential association between shift work with IBS/FD. Methods: We searched relevant observational studies on Medline (PubMed) and Embase until June 30, 2021. Two different investigators extracted data and assessed the quality of each study independently. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a study in Saudi Arabia, freelance employees who worked for more than nine hours were more likely to have IBS [ 7 ]. One meta-analysis reported that shift work is associated with IBS [ 17 ], and another meta-analysis of healthcare professionals found that in addition to shift work, poor sleep quality and female sex were also major contributors to the presence of IBS [ 18 ]. Shift work may also contribute to circadian disturbances.…”
Section: Features Of Work and Ibsmentioning
confidence: 99%
“…In a study in Saudi Arabia, freelance employees who worked for more than nine hours were more likely to have IBS [ 7 ]. One meta-analysis reported that shift work is associated with IBS [ 17 ], and another meta-analysis of healthcare professionals found that in addition to shift work, poor sleep quality and female sex were also major contributors to the presence of IBS [ 18 ]. Shift work may also contribute to circadian disturbances.…”
Section: Features Of Work and Ibsmentioning
confidence: 99%
“… 6 , 7 , 13 , 14 The association between IBS and shift work has been previously reported, and some meta-analyses indicate a higher prevalence of IBS among shift workers. 12 , 15 Various treatments for IBS, such as medication 16 and self-management programs, including CBT, 17 can improve the work productivity of individuals with IBS.…”
Section: Introductionmentioning
confidence: 99%